Peran dewan pengawas syariah dalam memitigasi risiko pada perbankan syariah - Hisyam, Naufal Nabih (Maliki Interdisciplinary Journal, 2026)
This study aims to analyze the role of the Sharia Supervisory Board in mitigating risks in Islamic banking, particularly sharia compliance risk. The rapid growth of the Islamic finance industry requires effective supervision to ensure that all operational activities comply with sharia principles. This research employs a qualitative approach through literature review. The findings indicate that the Sharia Supervisory Board plays a strategic role in risk mitigation through three main functions: preventive, detective, and corrective. In its preventive role, the SSB ensures that products and contracts comply with sharia principles from the planning stage. In the detective role, the SSB conducts continuous supervision and sharia audits. Meanwhile, in the corrective role, the SSB provides recommendations for improvements when violations occur. Additionally, the SSB contributes to the implementation of risk management and Good Corporate Governance (GCG). However, challenges remain, particularly the limited availability of human resources with dual competencies in sharia and modern banking. Therefore, optimizing the role of the SSB is essential to maintain stability, reputation, and public trust in Islamic banking.